PENGARUH PEMBERIAN JENIS DAN TAKARAN PUPUK ORGANIK TERHADAP KARAKTERISTIK FISIOLOGIS TANAMAN BAWANG MERAH PADA TANAH ULTISOL - Yuyun Rahmawati; Joko Purnomo; Hilda Susanti (EnviroScienteae, 2018)
This research was carried out from December to May 2018, at Greenhouse of Supervision and Certification of  Food Crops and Horticulture Banjarbaru. The objective of the study was to examine the effect of organic fertilizer type and dosage and to know the best dosage of each type of organic fertilizer on the physiological characteristics of shallots on ultisol soil. The experimental method is designed based on a two-factor nested design with Completely Randomized Compact Design (RAL) design. The first factor is the type of organic fertilizer (J) consisting of two levels namely cow dung (j1) and chicken manure (j2), the second factor is the organic fertilizer dosage nested in the organic fertilizer consisting of four levels of 10 t ha-1 (d1); 20 t ha-1 (d2); 30 t ha-1 (d3) and 40 t ha-1 (d4). Treatment was repeated 4 times, each experimental unit consisting of  3 polybags.  Observation variables were leaf N content, leaf chlorophyll content, the water content of bulbs and volatile oil content on bulbs. The results showed that the type and quantity of organic manure of cow dung and chicken manure had no significant effect on all observed variables. Limiting factors such as low light intensity are suspected to cause the type treatment and organic fertilizer dosage does not affect all observed variables. Light intensity and humidity during cultivation are incompatible with the requirements of shallots grow is also seen in the long period of vegetative shallots plant which is a manifestation of the plant's response to environmental conditions.